Long‐term efficacy of imepitoin in the treatment of naive dogs affected by idiopathic epilepsy. (5th August 2017) - Gallucci, A.; Gagliardo, T.; Menchetti, M.; Bianchi, E.; Bucci, D.; Gandini, G.
Abstract : The purpose of this study was to evaluate the long‐term (12 months) efficacy and tolerability of imepitoin as first‐choice treatment in 56 dogs suffering from idiopathic epilepsy and identify possible factors affecting the outcome. Primary treatment success (PTS) was defined as the achievement of a seizure‐free interval three times longer than the pretreatment interictal interval (at least three months). Secondary treatment success (STS) was achieved by a decrease in seizure frequency ≥50 per cent compared with the pretreatment frequency. In the long‐term follow‐up, PTS was recorded in 14 (25 per cent) dogs and responder‐dogs (PTS+STS) were 30 (54 per cent) showing significant reduction in the monthly average number of seizures (P<0.001). Median seizure frequency per month was 1.69 pretreatment and 0.3 at 12‐month follow‐up. Dogs with cluster seizures were significantly reduced (P=0.02). PTS at three and six months was associated with PTS (P=0.006 and <0.001, respectively) and with the status of responder dogs (P=0.002) at 12‐month follow‐up. Dogs aged >36 months at the start of imepitoin treatment had a positive association to become responder dogs (P<0.001) and achieve PTS (P=0.004). 16 dogs (29 per cent) discontinued imepitoin due to its inefficacy. The receiver operator curve highlighted ≥19 mg/kg twice a day as the most effective minimal dosage. Mild and transient side effects were observed in 16 dogs (29 per cent).